1989
DOI: 10.1002/ijc.2910430107
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of male breast cancer in scandinavia, 1943–1982

Abstract: Male breast cancer incidence was examined in a collaborative study of data from the cancer registries in Denmark, Finland, Norway and Sweden, comprising a total of 1,529 cases diagnosed from 1943 to 1982. Effects of age, time of diagnosis, birth cohort and country of residence were evaluated by using statistical models of the multiplicative Poisson type. The logarithm of incidence increased linearly with the logarithm of age and had a slope of about 5. In Denmark, male breast cancer incidence increased signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
31
0
4

Year Published

1996
1996
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 14 publications
5
31
0
4
Order By: Relevance
“…Thus, male reproductive tract development and testicular functions are undergoing important modifications which could be the result of changes in our environment. Finally, another study has shown an increase in male breast cancer, a rare pathology, in four Scandinavian countries (Ewetz et al 1989). The risk of breast cancer increases in women over fifty years of age, probably because they have been exposed to active estradiol for a long period of time (Marshall 1993).…”
Section: Introductionmentioning
confidence: 96%
“…Thus, male reproductive tract development and testicular functions are undergoing important modifications which could be the result of changes in our environment. Finally, another study has shown an increase in male breast cancer, a rare pathology, in four Scandinavian countries (Ewetz et al 1989). The risk of breast cancer increases in women over fifty years of age, probably because they have been exposed to active estradiol for a long period of time (Marshall 1993).…”
Section: Introductionmentioning
confidence: 96%
“…3 The prevalence of male breast cancer increases with age; the average age at diagnosis is 60 years old, which is 10 years greater than in women. 4 The incidence of breast cancer in men varies considerably by geographic location.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] The incidence of MBC, however, is rising and continues to increase by 1.1% yearly. 10 The American Cancer Society estimates that, in 2006, 1760 men will be diagnosed with breast cancer, and 460 men will die of the disease.…”
mentioning
confidence: 99%